The Response to Burn Injury in Mice With Human Hematolymphoid Systems. Issue 1 (January 2016) - Costantini, Todd W.; Meads, Morgan; Dang, Xitong; Coimbra, Raul; Torbett, Bruce E.; Baird, Andrew; Eliceiri, Brian P.
Abstract : Objective: To develop an animal model of injury that more closely represents the human inflammatory cell response to injury. Background: Because the mouse inflammatory response to burn injury cannot account for the contribution of human-specific genes, animal models are needed to more closely recapitulate the human inflammatory response and improve the translational impact of injury research. To this end, we hypothesized that the human inflammatory cell response to injury could be selectively assessed after severe burn injury using humanized mice. Methods: NOD-Scid-IL2Rγ null mice were transplanted with human hematopoietic CD34 + progenitor cells; their engraftment confirmed and then subjected to 30% total body surface area steam burn injury. Blood, bone marrow, and lung tissue were collected 4 hours after injury and human inflammatory cell mobilization analyzed using flow cytometry and immunohistochemistry. Results: Burn injury caused mobilization of human inflammatory cells into the systemic circulation. Next, burn injury was accompanied by evidence of histologic lung injury and concomitant mobilization of human CD45 + immune cells into the lung that were associated with increased trafficking of human CD11b + myeloid cells. Conclusions: These experiments are the first to demonstrate the suitability of humanized mice for injury research. They offer the possibility to address very specific research questions that are not amenable to traditional mouse models of injury, for example, the emerging role of certain human-specific genes that are either unrepresented or totally absent, from the mouse genome.